2013
DOI: 10.1208/s12249-013-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of Co-Processed Non-Ionic Surfactants in Enhancing Permeability of a Model Hydrophilic Drug

Abstract: Paracellular route is a natural pathway for the transport of many hydrophilic drugs and macromolecules. The purpose of this study was to prospectively evaluate the ability of novel co-processed non-ionic surfactants to enhance the paracellular permeability of a model hydrophilic drug metformin using Caco-2 (human colonic adenocarcinoma) cell model. A three-tier screen was undertaken to evaluate the co-processed blends based on cytotoxicity, cellular integrity, and permeability coefficient. The relative contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…The TEER results confirmed the intactness of the monolayers prior to the commencement of the transport experiments (all cell monolayers exhibited TEER > 250 Ω). There was, however, a decrease in the TEER values upon the application of test compounds to the cells, which may be an indication of temporary tight junction changes [19] due to the change in environment. The TEER values are shown in ▶ Table 2.…”
Section: Resultsmentioning
confidence: 95%
“…The TEER results confirmed the intactness of the monolayers prior to the commencement of the transport experiments (all cell monolayers exhibited TEER > 250 Ω). There was, however, a decrease in the TEER values upon the application of test compounds to the cells, which may be an indication of temporary tight junction changes [19] due to the change in environment. The TEER values are shown in ▶ Table 2.…”
Section: Resultsmentioning
confidence: 95%
“…In the case of human psoriatic dermal fibroblasts, 0.5 mM TR still had an antiproliferative effect, while for human normal dermal fibroblasts 0.1 mM and 0.01 mM concentrations were poorly effective [ 48 ]. In the study conducted by Alvi and Chaterjee, TR showed an IC 50 value of 2.0 ± 0.35% ( v/v ) when tested against Caco-2, while Labrasol (another non-ionic surfactant) was much more toxic (IC 50 0.22 ± 0.01%) to this line [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the Caco‐2 monolayer is disrupted, the lucifer yellow will leak into the basolateral compartment. With a MW approximately 457 g/mol, lucifer yellow is a relatively small molecule that is used as a marker of paracellular transport since it cannot pass across the cellular membrane (Alvi & Chatterjee, ).…”
Section: In Vitro Methods To Study Transportersmentioning
confidence: 99%